Penguatan Literasi Keluarga di Kecamatan Curug Tangerang Banten - Ifina Trmuliana; Raeh Niken Baghiroh Raeh; Riri Awaliyah (Universitas Tangerang Raya, 2022)
The literacy interest of the Indonesian people is currently relatively low, this is influenced by one of them because of the lack of early literacy recognition. This study aims to determine the form of family literacy in Curug sub-district, Tangerang Banten. This research uses a qualitative approach with a case study method and uses a Campbell matchmaking data analysis technique. The results of data analysis found that the form of family quality in Curug sub-district, Tangerang Banten, was through providing a reading corner at home, reading with children, listening to children tell stories and getting used to reading routines every day.